2018
DOI: 10.1186/s12903-018-0542-2
|View full text |Cite
|
Sign up to set email alerts
|

Dental health between self-perception, clinical evaluation and body image dissatisfaction – a cross-sectional study in mixed dentition pre-pubertal children

Abstract: BackgroundSelf-perception of oral health status is a multidimensional construct that includes psychological, psychosocial and functional aspects of oral health. Contemporary concepts suggest that the evaluation of health needs should focus on clinical standards and socio-dental indicators that measure the impact of health/disease on the individual quality of life. Oral health cannot be dissociated from general health. This study evaluates a possible association between oral health status, body size, self-perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…The association between clinical consequences of untreated dental caries and poor self-rated oral health suggests the long-term consequences of dental caries and their sequelae that remain untreated, predominantly resulting in odontogenic infections, influencing adolescents' perception of oral health. Although there is little evidence on this topic, the relationship between restorative treatment needs and self-perceived oral health has been reported [Banu et al, 2018], reinforcing the hypothesis that neglecting treatment of cavitated dental carious lesions in adolescents can negatively impact on their perception of oral health.…”
Section: Discussionmentioning
confidence: 88%
“…The association between clinical consequences of untreated dental caries and poor self-rated oral health suggests the long-term consequences of dental caries and their sequelae that remain untreated, predominantly resulting in odontogenic infections, influencing adolescents' perception of oral health. Although there is little evidence on this topic, the relationship between restorative treatment needs and self-perceived oral health has been reported [Banu et al, 2018], reinforcing the hypothesis that neglecting treatment of cavitated dental carious lesions in adolescents can negatively impact on their perception of oral health.…”
Section: Discussionmentioning
confidence: 88%
“…The findings rejected the study hypothesis because, even when the quality of life was evaluated based on the item levels, the anterior occlusal characteristics in the mixed dentition had no impact on the OHRQoL. Previous studies 3,4,7,8,[20][21][22][23][24][25][26][27][28][29] showed that an increased overjet and increased spacing, especially a midline diastema, were the conditions that most affected the individual, regardless of age. Still, the older children become, the more their malocclusion affects their a Values are given as n (%).…”
Section: Discussionmentioning
confidence: 87%
“…1 Mixed dentition is a transitional stage, characterized by a wide range of occlusal variations 2 and a high prevalence of malocclusion. 1,[3][4][5][6][7] In addition, occlusal conditions, such as increased overjet, deep overbite, dental crowding, and spacing, are malocclusions usually associated with dissatisfaction with dental appearance. 4 However, studies addressing the impact of occlusal conditions in the mixed dentition only quantified malocclusion 3,7-9 and did not consider the physiological changes inherent in this stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can result in malnutrition due to alterations in diet, and phonation problems, especially in the older age group [ 10 ]. There is also higher body dissatisfaction [ 11 ] and simple acts of smiling, communicating and eating can be affected negatively [ 12 ]. Hence, oral health not only affects one’s general health, but also has an impact on mental health.…”
Section: Introductionmentioning
confidence: 99%